"If the Gospel We Preach Disregards Human Rights, I Would Rather not Preach This Gospel": Towards a Lived Theology of Hong Kong Churches. Issue 4 (January 2023) - Chu, Ann Gillian; Perry, John
Both pro-establishment Christians, who support 'obeying the authority' (Romans 13), and pro-democracy Christians, who participated in the 2014–20 protests, want what is best for Hong Kong and truest to their Christian faith, but they understand those aims differently. The former believe social stability is a way to create space for Christian faith to flourish, while the latter judge that we need to break the current unjust system for Christian faith to begin flourishing. After conducting interviews with lay Christians, we found that both sides can struggle to communicate their vision for faithful Christian political theology. One reason, which we explore here, is that the key theo-political concepts at issue—namely, protest, democracy, and rights—derive from the historical context of post-Christendom societies rooted in the Western Enlightenment tradition. Hong Kong is adjacent to that tradition, but not at home in it. Using the method of 'narrative portraiture, ' we endeavor to explore their respective theologies. This method uses the participants' own stories, so that we, as researchers, are not speaking for Hong Kong Christians, but instead illuminating their own ideas. Presenting these lived theologies can remind us, as church leaders, that our congregations are a source of God's revelation to us, even when they may lack the terms to communicate effectively, which is why we should not forget to listen to the "average Jane."